Synthesis and characterizations of ZnO thin films deposited on aluminum metal substrate by sol-gel spin coating technique - Shaitir, Ali; Sutjipto, A. G. E.; Y., Shian (Universiti Malaysia Pahang, 2018)
In this work, zinc oxide (ZnO) thin films were synthesized on aluminum substrate using sol-gel spin coating technique. The effect of changing in the annealing temperature (from 300 ◦C to 500 ◦C) and the rates of spin (from 1000rpm to 2000rpm) on the structural, optical and piezoelectric properties of the produced films are studied. Zinc acetate dehydrate, absolute ethanol and diethanolamine were used to act as sol gel precursor. Sol gel was coated on glass slide which wrapped by aluminum. The thin film was formed after preheating and annealing. The thin film was characterized by X-ray diffraction (XRD), Photoluminescence Spectroscopy (PL) and Ultraviolet-visible Spectroscopy (UV-Vis). X-ray analysis showed that thin films were preferentially diffracted around 65° which corresponding to (1 1 2) diffraction phase. From the PL results, there was only film with spin speed of 2000 rpm and annealing temperature of 300°C had slightly left wavelength which was 380 nm. Annealing temperature would affect only the intensity of PL wavelength. From the results of UV-Vis, it was observed that when the spin speed was increased at same annealing temperature, the band gap was decreased. When the annealing temperature was increased at same spin speed, the band gap was decreased. This work provides a low cost and environment friendly material for Vibration sensing applications.